Pengembangan Aplikasi Pembelajaran Pendidikan Jasmani Olahraga dan Kesehatan Berbasis Pada Android Sekolah Menengah Atas Kelas XI Kabupaten Kudus - Affan Suko Handoyo; Husnul Hadi; Dian Ayu Zahraini (Journal of Physical Activity and Sports (JPAS), 2023)
This research background is an innovation of developing physical education learning applications for health and sport. With the development of practice applications, this was hoped that it could assist improving students' interest. This research problem was how to develop “E- PENJASKES” in physical, health, and sports learning. The goal of his research is to develop sports and health physical applications as learning aid applications that could provide effectiveness for both learners and teachers. This device is applied in learning basic techniques in sports learning so as in facilitating teacher performances. Kind of this research is R and D. The study used steps, such as identification of the problems, product designs and manufacturers, expert validations, product revisions, and final products. Development of “E- PENJASKES” was the first validated by both materials and media experts, and also 90 and 300 learners for the initial field trial, and 325 learners for the operational field trial. This research subjects were students of senior high school at twelve class in Kudus district. In collecting data, the researcher applied the instruments in a questionnaire pattern. The technique of analysis data used descriptive qualitative and quantitative. This research results showed that the “E- PENJASKES” application was feasible to be used as an application in sports learning. Those results were obtained based on results of validation, such as a) media expert of 87. 5% named feasible; b) materials expert of 80 % named suitable; c) the operational field trial learners were 97. 35% named feasible. Whereas, all could be asserted that the “ Application of “E- PENJASKES” has been declared appropriate to be used as a sport and healthy physical learning.